Trace Determination of Tamoxifen using Optimized Solvent Bar Microextraction and HPLC-UV - Behbahani, Persia; Ghasemi, Nahid; Qomi, Mahnaz; Tahvildari, Kambiz (Current Pharmaceutical Analysis, 2020)
Background: Tamoxifen (Soltamox) is an antineoplastic agent and an estrogen receptor antagonist used to treat breast cancer, but have severe side effects such as hot flashes, vaginal discharge, etc. Dose monitoring is a necessity for optimum treatment, to prevent severe adverse effects. Methods: In this study, the solvent bar microextraction method (SBME) was used for preconcentration and microextraction coupled with High-performance liquid chromatography-ultraviolet (HPLC-UV) analysis of tamoxifen. Results: The limit of detection and limit of quantification were 13.3 and 40 μgL-1, respectively. The linear range was between 40 and 10000 μgL-1 with a correlation coefficient of 0.999. The enrichment factor was 169 and the relative standard deviation within-day and between-day were 3.6 and 4.0, respectively. Conclusion: The use of sensitive SBME method coupled with HPLC-UV analysis for detection of tamoxifen at trace level proved to be successful, offering a desirable preconcentration factor, and a costeffective and green set-up for determining its rate of elimination from cancer patients and wastewater.
Keywords: Tamoxifen